O trabalho infantil e as políticas públicas para sua erradicação no Brasil: o pensar sobre a infância e a educação - Fortunato, Sarita Aparecida de Oliveira (2016)
This research analyzes public policies for the eradication of child labor in Brazil and the relationship among schools, the Guardianship Council and public power in terms of the guarantee of full protection of childhood and adolescence. Dealing with child labor and the social role of public schools – theme of this thesis – in order to better understand them is a fundamental factor for childhood assistance, when education is understood as a sine qua non element for human formation and for the understanding of child labor as the violation of rights, marked by contradictions, undefined issues and deadlocks. The challenge for education is to create spaces that provide experiences that consider the specific nature of childhood, its cultural determinations and human rights supported by the Brazilian Federal Constitution and by Law n. 8.069 from 1990, Child and Adolescent Statute (ECA, in the Portuguese acronym). This study is based on the discussion about childhood, education and human rights. It takes into consideration the relationship between childhood and society as a critical-historical expression against a “culture of barbarity”. The main aim is to analyze public policies for the eradication of child labor in Brazil, understood as the fixation of constituent values in terms of assisting the needs of childhood in its full school formation. The study methodology is based on dialectic logic, which analyzes the movement between theory and empirical data from field research. For the collection of empirical data semi-structured interviews were conducted with 30 professionals linked to the protection and defense of childhood human rights in the municipality of Curitiba, PR; 15 professionals who were Coordinators of the Protection Network in Education; 12 Guardianship Councilors; 2 professionals from Special Social Assistance to Childhood and the Regional Labor Public Office. The data was analyzed under five categories: Childhood; Child Labor; Public Policies for the Eradication of Child Labor and the Social Role of Public Schools. The results highlight the need for effective actions from civil society and from the public power that fight against and supervise the forms of child labor in the country. The study concludes that it is indispensable to continue with the investigations in the spotted areas and similar contexts, the presentation of effective solutions for the problems identified; the establishment of public policies that aim to supervise the context of the articulations between public policies for childhood and the unveiling of social contradictions; the reflective analysis about these and other paradoxes in terms of how to deal and overcome the barriers imposed by the exploration of childadolescent labor.